Processes linking cultural ingroup bonds and mental health: the roles of social connection and emotion regulation - Roberts, Nicole A.; Burleson, Mary H. (Frontiers in Psychology, 2013)
Cultural and ethnic identities influence the relationships individuals seek out and how they feel and behave in these relationships, which can strongly affect mental and physical health through their impacts on emotions, physiology, and behavior. We proposed and tested a model in which ethnocultural identifications and ingroup affiliations were hypothesized explicitly to enhance social connectedness, which would in turn promote expectancy for effective regulation of negative emotions and reduce self-reported symptoms of depression and anxiety. Our sample comprised women aged 18 to 30 currently attending college in the Southwestern US, who self-identified as Hispanic of Mexican descent (n=82; MAs) or as non-Hispanic White/European American (EAs; n=234) and who completed an online survey. In the full sample and in each subgroup, stronger ethnocultural group identity and greater comfort with mainstream American culture were associated with higher social connectedness, which in turn was associated with expectancy for more effective regulation of negative emotions, fewer depressive symptoms, and less anxiety. Unexpectedly, preference for ingroup affiliation predicted lower social connectedness in both groups. In addition to indirect effects through social connection, direct paths from mainstream comfort and preference for ingroup affiliation to emotion regulation expectancy were found for EAs. Models of our data underscore that social connection is a central mechanism through which ethnocultural identities—including with one’s own group and the mainstream cultural group—relate to mental health, and that emotion regulation may be a key aspect of this linkage. We use the term ethnocultural social connection to make explicit a process that, we believe, has been implied in the ethnic identity literature for many years, and that may have consequential implications for mental health and conceptualizations of processes underlying mental disorders.